Ovarian hyper stimulation syndrome: a case report - Patidar, Arti; Bhati, Balgopal Singh; Bhati, Indra (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
We present here a rare case ovarian hyper stimulation syndrome. In the case patient came with complain of abdominal pain, distension, nausea, vomiting with known case of secondary infertility.